Finger Millet [Eleusine coracana (L.) Gaertn.] Improvement: Current Status and Future Interventions of Whole Genome Sequence - Antony Ceasar, S.; Maharajan, T.; Ajeesh Krishna, T. P.; Ramakrishnan, M.; Victor Roch, G.; Satish, Lakkakula; Ignacimuthu, Savarimuthu (Frontiers in Plant Science, 2018)
The whole genome sequence (WGS) of the much awaited, nutrient rich and climate resilient crop, finger millet (Eleusine coracana (L.) Gaertn.) has been released recently. While possessing superior mineral nutrients and excellent shelf life as compared to other major cereals, multiploidy nature of the genome and relatively small plantation acreage in less developed countries hampered the genome sequencing of finger millet, disposing it as one of the lastly sequenced genomes in cereals. The genomic information available for this crop is very little when compared to other major cereals like rice, maize and barley. As a result, only a limited number of genetic and genomic studies has been undertaken for the improvement of this crop. Finger millet is known especially for its superior calcium content, but the high-throughput studies are yet to be performed to understand the mechanisms behind calcium transport and grain filling. The WGS of finger millet is expected to help to understand this and other important molecular mechanisms in finger millet, which may be harnessed for the nutrient fortification of other cereals. In this review, we discuss various efforts made so far on the improvement of finger millet including genetic improvement, transcriptome analysis, mapping of quantitative trait loci (QTLs) for traits, etc. We also discuss the pitfalls of modern genetic studies and provide insights for accelerating the finger millet improvement with the interventions of WGS in near future. Advanced genetic and genomic studies aided by WGS may help to improve the finger millet, which will be helpful to strengthen the nutritional security in addition to food security in the developing countries of Asia and Africa.